Usage of blood products in emergency department at tertiary care centre - Hanumanthaiah, Ramesh Gorghatta; Prasad, Dheemantha; Krishnappa, Panchakshari Prasanna Bangalore; R., Sreelatha (International Journal of Advances in Medicine, 2017)
Background: Blood usage in the emergency department is a formidable challenge to the treating doctor. Inadvertent use of blood can do more harm to the patient than good. Analyzing blood transfusion data will help in formulating policies for transfusion in Emergency medicine department. The present study is taken to formulate guidelines for transfusion in Emergency department of our hospital. The present study also helps us to analyze the blood requirement, utilization and wastage in Emergency department, Victoria hospital. Methods: The study done was a prospective study over a period of three months from March 2016 to May 2016. A descriptive, prospective study was conducted with a total of three hundred cases collected from the Emergency department (Casualty), Victoria hospital. Results: Commonest indication for packed red cell transfusion was anemia, for FFP was hypoproteinaemia and for platelet concentrate was viral hemorrhagic fever. Transfusion trigger for packed red cells is haemoglobin of less than 7gram/dl with no co-morbid conditions and 7-9 gram/dl when there are co-morbid conditions. Conclusions: A protocol has to be formulated to reduce the wastage and to effectively utilise blood and its products.